Prevalence of Aphid-Transmitted Potyviruses in Pumpkin and Winter Squash in Georgia, USA - Nirmala Acharya; Manish Kumar; Sudeep Bag; David G. Riley; Juan C. Diaz-Perez; Alvin M. Simmons; Timothy Coolong; Theodore McAvoy (Viruses)
Viruses are a major pathogen challenging the sustainable production of cucurbits worldwide. Pumpkin and winter squash showed severe virus-like symptoms during the fall of 2022 and 2023 in Georgia, USA. Symptomatic leaves were collected from the field and processed for small RNA sequencing for virus identification using high-throughput sequencing (HTS). HTS analysis revealed the presence of two aphid-transmitted viruses (ATVs), zucchini yellow mosaic virus (ZYMV) and papaya ringspot virus (PRSV), along with three whitefly-transmitted viruses, cucurbit chlorotic yellows virus, cucurbit yellow stunting disorder virus, and cucurbit leaf crumple virus. The results of our study suggest a significant shift in ATV’s abundance in these two crops between 2022 and 2023. According to the qPCR data in the fall of 2022, pumpkins experience an incidence of 56.25% and 31.25% of PRSV and ZYMV, respectively. Similarly, winter squash shows an incidence of 50% and 32.14% of PRSV and ZYMV, respectively. Mixed infection of both viruses was also observed in these two crops. In 2023, we observed a predominance of ZYMV in pumpkin and winter squash (61.25% and 42.50%, respectively). However, PRSV was not detected in pumpkins, and it was detected at a negligible level (0.62%) in winter squash using qPCR. Phylogenetic analysis of ZYMV-encoded coat protein (CP) and helper component-protease (HC-Pro) from Georgia suggests a close relationship with the European isolates. Conversely, PRSV-encoded CP and NIa-VPg show a more diverse evolutionary history. Overall, this research will provide valuable insights into the dynamics of ZYMV and PRSV in pumpkin and winter squash crops within the southeastern United States.